Financial Innovation and Money Demand: Application to Chile and Mexico - Arrau, Patricio; Gregorio, Jose De (The Review of Economics and Statistics, 1993)
This paper reexamines one estimation of money demand equations using quarterly data for Chile and Mexico. The authors find no evidence of cointegration of traditional long-run money demand equations. In light of this evidence, they argue that there is an important permanent component of the demand for money not captured by traditional variables (interest rates and income). The authors call this phenomenon financial innovation and they include it in the traditional specification by assuming that it follows a random walk. Copyright 1993 by MIT Press.